Semarak Milad KOHATI 58th Dialog Peran Perempuan dalam Dunia Kesehatan ”Perempuan Berdaya, Kesejahteraan Holistik Membanguan Generasi Sehat” - Ummul Khair; Nunung Erviany; Ummu Kalsum; Syarifah Sahirah; Hasnia Hasnia; Hajar Hajar; Nur Rahmah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
In commemoration of KOHATI's (Korps HMI Wati) Milad, known as a special body of the Islamic Student Association (HMI) tasked with nurturing, developing, and enhancing the potential of women in women's movements, KOHATI plays several roles. These include helping to build awareness among Muslims, improving the quality of education, encouraging women's participation in politics, shaping good leadership character, and enhancing community welfare. The celebration of KOHATI’s Milad provides an opportunity for the people of Soppeng, especially the youth in Soppeng Regency, to broaden their knowledge about the role of women in the health sector, particularly reproductive health. Through this approach, we hope that the people of Soppeng will become more open and concerned about issues related to reproductive health. Reproductive health is a right for every woman. Do not hesitate to seek information and access the services you need. Education is power. With knowledge, women can empower themselves and protect both themselves and future generations